(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
It is predicted that the world’s primary energy demand would rise to 37% higher by the year 2040, and this would consequently increase current pressures on the global energy system. This would in turn make renewable energy more viable against non-depletable and sustainable energy. Malaysia has made an effort to meet this energy forecast by reducing the reliance on biomass for energy production, and is committed in making it a reality. The ocean thermal energy-driven development based on the ocean thermal energy conversion technology (OTEC) has great potential in leading the Malaysian renewable energy industry. However, this cannot effectively take place until certain legal impediments are identified. Thus, a legal analysis must be conducted to provide the Malaysian government or any government authority in the world to be aware of such legal impediments in ensuring success of their OTEC venture. Given the industry is at its infant stage, such a legal review is hoped to eventually promote further legal analysis on OTEC-related activities.